From Reporting to Responsibility: Legal Innovations in Corporate Law and Governance under the examples of the EU's “Corporate Sustainability Reporting Directive (CSRD)” - Magda Ositashvili (European Scientific Journal, ESJ, 2025)
The topic of this research is as practical as it is theoretical and cognitive. It is based on the example of the EU's Corporate Sustainability Reporting Directive (CSRD). The practical relevance of the research issue is considered in terms of global environmental, social, labour and governance issues, as well as regulatory issues, which have affected the entire EU and given rise to the need for a mechanism to protect corporations from inefficient outcomes and create a more transparent, accountable and sustainable corporate environment within the EU. In the modern digital era, companies have started to act for sustainability after facing the failures of corporations to make efficient reporting efforts, which leads to poor risk management, increased costs and decreased innovation. However, it is obvious that the global community has not created the mechanisms that would vitally promote sustainable economic development over the last decade. In the paper Principles of Political Economy by the renowned English philosopher John Stuart Mill, we read that 'the most cogent reason for establishing a rule of conduct is that it promotes general happiness; it has been found to do so by experience, and that constitutes its title to be respected as a rule'. In order to improve transparency and accountability within companies, promote sustainable business practices, support informed decision-making and contribute to the EU's Green Deal, the EU consolidated the directive, the meaning of which is considered within the context of recent history (Guerman, 2021). The Volkswagen emissions scandal (also known as 'Dieselgate', 2015) revealed the problem of environmental degradation when it was discovered that the company had installed software in its diesel vehicles to cheat emissions tests. This allowed the cars to emit nitrogen oxides at levels up to 40 times higher than the legal limit. The scandal has highlighted the need for greater transparency and accountability in corporate environmental practices. Similarly, Amazon has faced ongoing criticism for its labor practices, including reports of harsh working conditions, inadequate breaks and high injury rates in its warehouses (Guerman, 2021). Repeated investigations and media reports have brought these issues to light, demonstrating the need for greater transparency and accountability in how companies treat their employees. However, the legal process is ongoing.  In 2018, Facebook faced intense scrutiny following the Cambridge Analytica scandal, in which the personal data of millions of users was harvested without consent and used for political advertising. The lack of transparency in data handling practices and inadequate accountability measures were widely discussed, highlighting the need for more robust reporting and user privacy protection. These examples illustrate the diverse range of problems that corporations have faced, demonstrating the urgent need for the EU's Corporate Sustainability Reporting Directive. The dilemmas between 'reporting' and 'responsibilities' are evident in the market, and the legal and economic analysis of innovations in the corporate sustainability process is a fascinating area of research.